2000
DOI: 10.1021/jp9934634
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Urea with Cu+in the Gas Phase:  An Experimental and Theoretical Study

Abstract: The gas-phase reactions between Cu + and urea have been investigated by means of mass spectrometry techniques. The primary products formed in the ion source correspond to [urea-Cu] + , [(urea) 2 -Cu] + , and [Cu + ,C,N 2 ,H 2 ] complexes. The MIKE spectrum of [urea-Cu] + complex shows several spontaneous losses, namely, NH 3 and HNCO. A very weak peak corresponding to the loss of H 2 O is also observed, as well as a minor fragmentation of the adduct ion to yield Cu + . The structures and bonding characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
49
2
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 41 publications
6
49
2
3
Order By: Relevance
“…In this respect, it is also important to emphasize that these linear arrangements were also found to be the most stable complexes formed in the gas-phase reactions between Cu + and a series of neutrals as formamide, 42 guanidine, 43 or urea. 44 It is also important to note that, in general, the open forms produced by C5-O5 bond fission (OG2) are systematically lower in energy than those formed by the cleavage of the C1-O5 bond (OG1 or OG3). In fact, the OG2a structure is estimated to be 118.5 kJ mol -1 more stable than the OG1a form.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, it is also important to emphasize that these linear arrangements were also found to be the most stable complexes formed in the gas-phase reactions between Cu + and a series of neutrals as formamide, 42 guanidine, 43 or urea. 44 It is also important to note that, in general, the open forms produced by C5-O5 bond fission (OG2) are systematically lower in energy than those formed by the cleavage of the C1-O5 bond (OG1 or OG3). In fact, the OG2a structure is estimated to be 118.5 kJ mol -1 more stable than the OG1a form.…”
Section: Resultsmentioning
confidence: 99%
“…To date, most efforts to determine the intrinsic reactivity of cationized small model biomolecules [4][5][6][7][8] have concentrated on singly charged ions, in spite of the biochemical importance of interactions with multiply charged ions. This is exemplified by the combined theoretical and experimental studies on reactions of glycine with Ni + and Cu + , which showed that the most important reactive pathways are those leading to the loss of H 2 O, CO and [C,H 2 ,O 2 ].…”
mentioning
confidence: 99%
“…It might be due to two possible reasons. One was that N-compound poisoned the metal catalyst which led to the inhibition of PCDD/Fs chlorination process (Lippert et al 1991;Luna et al 1997;Luna et al 2000). Another reason might be that N-compound reacted with chlorine to reduce the substitution of hydrogen atom (Kuzuhara et al 2005).…”
Section: Resultsmentioning
confidence: 99%